A Simulated Model of a Triple Band Patch Antenna Proposed for Vital Signs Monitoring Equipment - Anfal Shukur Taher; Rashid Ali Fayadh; Abbas Fadhal Humadi; Aaraf Shukur Alqaisi; Mohd Fareq Abd Malek (Journal of Techniques)
In the modern lifestyle, an increase in psychological pressures was observed, leading to an increase in various diseases, which increased the need for diagnosis and treatment, (i.e., increased demand for) equipment to monitor vital activities, Therefore, a microstrip patch antenna was suggested as the topic of this article because it is popular in wireless systems due to its low cost, lightweight, and thin profile. The proposed design is made of FR-4 as a substrate material, and copper for the patch and the ground. The reader can notice that our proposed antenna owns the following resonance frequencies: (3.68), (6.48), and (7.93) GHz respectively. The gain values for the previous resonance frequencies were respectively (27) dBi, (11.1) dBi, and (4.19) dBi, while the values of directivity were (32.17) dBi, (15.70) dBi, and (7.984) dBi. The radiation efficiency values were (-5.179) dB, (-4.561) dB, and (-3.789) dB, while the values of the total efficiency were (-5.207) dB, (-4.631) dB, and (-3.799) dB The operating bandwidths were: (0.1146) GHz, (0.2764) GHz, and (0.3641) GHz. The design was simulated with CST software.